1987
DOI: 10.1002/clc.4960100712
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary right coronary artery

Abstract: Summary:A rare case of a patient with supernumerary right coronary artery in whom the two vessels arose from the right coronary sinus from two separate ostia adjacent to each other is presented. The smaller vessel gave off the sinoatrial nodal branch and the posterior descending artery whereas the larger one gave off the conus branch, the right ventricular branches, and continued as acute marginal branch. This is the first case report in the English literature. no cardiomegaly, and prominent aorta and upper lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Until the times that these letters were sent to the journal double RCA had been reported 15 times and in 17 cases (Table 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Both authors failed to mention about the papers by Gupta et al [4], Kunimasa et al [17] and Lemburg et al [18] in their letters.…”
Section: Dear Editormentioning
confidence: 83%
See 2 more Smart Citations
“…Until the times that these letters were sent to the journal double RCA had been reported 15 times and in 17 cases (Table 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Both authors failed to mention about the papers by Gupta et al [4], Kunimasa et al [17] and Lemburg et al [18] in their letters.…”
Section: Dear Editormentioning
confidence: 83%
“…However, the case reported by Gupta et al [4] which was the first report of double RCA in the literature had also two RCAs originating from separate ostia. In addition, Karabay et al referenced their report mentioning about the number of cases of reported double RCAs until that time by the paper by Erbagci et al [15].…”
Section: Dear Editormentioning
confidence: 92%
See 1 more Smart Citation
“…A double RCA was first reported in 1987 by Gupta et al [14]; in their study, the two vessels arose from the right coronary sinus from two separate ostia adjacent to each other, whereas the smaller vessel gave off the sinoatrial nodal branch and the posterior descending artery and the larger one gave off the conus branch, the right ventricular branches, and continued as acute marginal branch. A double RCA is an extremely rare congenital variant with only nine reported cases so far [15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 96%
“…Gupta et al [17] was the first to report incidence of a double RCA. In their study, the two vessels arose from separate adjacent coronary ostia with the smaller vessel providing the PIB and the larger vessel continuing as the right marginal branch [23].…”
Section: Introductionmentioning
confidence: 99%